Efficiency of AC vs. DC distribution systems in commercial buildings - Santos, Arthur Felício Barbaro dos, author; Young, Peter, advisor; Zimmerle, Daniel, advisor; Cale, James, committee member; Clark, Maggie, committee member (Colorado State University. Libraries, 2022)
Decarbonization and modernization of the grid, electrification of transportation, and energy storage are some of the trends pushing towards the significant growth of power electronics in the past few decades. The massive application of such devices has increased the interest in direct current (DC) power distribution as an alternative to the conventional alternating current (AC) distribution systems in residential and commercial buildings. This increase in non-linear loads, however, substantially increases current harmonics, which compromises the lifespan, efficiency, and/or operability of distribution components, such as transformers and protection equipment. Additionally, when comparing the efficiency of AC vs. DC distribution systems, the literature is often based on simulation studies rather than real measured data. In this regard, this study focuses on three major topics: a) Harmonic cancellation within building circuits; b) Endpoint use efficiency comparison for AC and DC in-building distribution systems; and c) A cautionary note on using smart plugs for research data acquisition. The analyses are based on recorded power consumption data from office-based appliances, made by smart plugs, combined with detailed characterization of sampled Miscellaneous Electric Loads (MELs') power converters. While harmonic cancellation studies often assume that AC converters operate across their rated power range, measured realistic power profiles reported in this work show that MELs operate below 40% of rated power the majority of the time when not in standby mode. This makes the harmonic cancellation significantly lower than that predicted when using full-range power assumptions, which could provide incorrect guidance to building design engineers. In contrast, increased diversity of MELs increases harmonic cancellation. Blending typical office loads with lighting, for instance, improves the harmonic cancellation to near the levels predicted by traditional methods. Regarding the endpoint efficiency of AC and DC distribution systems, no systematic efficiency advantage was found, when endpoint AC/DC converters were compared to a similar, commercially available, DC/DC converter powering the same load profile. That goes in the opposite direction of prior studies, which estimate converters' efficiency based on datasheet information or the efficiency at rated load.
Keywords: commercial buildings; DC/DC converters; smart plugs; DC distribution; AC/DC converters; miscellaneous electric loads